Sweetpotato as an alternative crop for vegetable growers in Marabá-PA - Mello, Alexandre Furtado Silveira; de Souza, Mazilene B; da Silva, Giovani O.; Pedroso, Maria Thereza M.; Santiago, Alailson V.; de Carvalho, José Luiz V. (FapUNIFESP, 2023)
The north region of Brazil has been experiencing agricultural and urban expansion leading to the need for economic alternatives to reduce deforestation and to increase food supply. One possibility is the cultivation of vegetables that are easily grown such as the sweetpotato. The objective of this work is to assess the performance of sweetpotato genotypes in three different planting seasons in Marabá, Brazil. Sweetpotato genotypes were evaluated using randomized block experimental design and at harvest time the final plant stand and the commercial root production were evaluated. Clone 11 was the most productive one in all planting dates, with commercial yield ranging from 80.4 to 127 t/ha. Canadense also was very productive and among the top yielding genotypes. CIP BRS Nuti’s commercial yield was similar to Beauregard’s in the two initial growing seasons but higher in the third planting cycle. The first season, that had high moisture during harvest time, presented the lowest root quality. However, in general, all cultivars performed well, being good options for growers to produce a food source with high quality and yield in small areas.